2000
DOI: 10.1292/jvms.62.521
|View full text |Cite
|
Sign up to set email alerts
|

Hump Attachment Structure of the Two-Humped Camel(Camelus bactrianus).

Abstract: ABSTRACT. The hump attachment structure was morphologically examined in the two-humped camel (Camelus bactrianus). The cranial hump is fixed by the trapezius and rhomboid muscles in the thoracic region. The strong collagen sheet in the basement of the hump is attached to the segmented bellies of the trapezius muscle, and the thoracic rhomboid muscle and the nuchal-supraspinous ligament support the attachment function of the trapezius muscle. The basement sheet possesses the line structure of collagen fibers, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Elsewhere, the hump stand erects during summer and was deviated to a side in winter. The shape of the humps of Mongolian Bactrian were small and Pyramid Shaped (Endo et al, 2000) while those of Ladakh Bactrian were distinctly large and irregular. However, the measurement of the hump is a quite debatable parameter to distinguish the phenotypes because the hump is the main fat storage form in camel representing on average 85% of the adipose tissue (Faye et al, 2001a) and its volume is linked to the body condition score which is not under genetic dependence, but linked to the feeding status of the animals (Kamili et al, 2006).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Elsewhere, the hump stand erects during summer and was deviated to a side in winter. The shape of the humps of Mongolian Bactrian were small and Pyramid Shaped (Endo et al, 2000) while those of Ladakh Bactrian were distinctly large and irregular. However, the measurement of the hump is a quite debatable parameter to distinguish the phenotypes because the hump is the main fat storage form in camel representing on average 85% of the adipose tissue (Faye et al, 2001a) and its volume is linked to the body condition score which is not under genetic dependence, but linked to the feeding status of the animals (Kamili et al, 2006).…”
Section: Resultsmentioning
confidence: 89%
“…Regarding the height up to wither, Endo et al (2000) reported that the Mongolian Bactrian was higher at the level of hump (7 feet i.e 213.26 cm) than Ladakh Bactrian.…”
Section: Resultsmentioning
confidence: 99%